Apple Fermented Products: An Overview of Technology, Properties and Health Effects - Guiné, Raquel P. F. (2021)
As an easily adapted culture, with overloaded production in some parts of the globe, ap- ples and their by-products are being redirected to pharmaceutical, canning and beverages indus- tries, both alcoholic and non-alcoholic. Fermentation is generally considered to increase the bioa- vailability of bioactive compounds found in apple, by impacting, through a high degree of changes, the product’s properties, including composition and health-promoting attributes, as well as their sensory profile. Probiotic apple beverages and apple vinegar are generally considered as safe and healthy products by the consumers. Recently, contributions to human health, both in vivo and in vitro studies, of non-alcoholic fermented apple-based products have been described. This review highlighted the advances in the process optimization of apple-based products considering vinegar, cider, pomace, probiotic beverages and spirits’ technologies. The different processing impacts on physical-chemical, nutritional and sensory profiles of these products are also presented. Addition- ally, the harmful effects of toxic compounds and strategies to limit their content in cider and apple spirits are illustrated. New trends of fermented apple-based products applicability in tangential in- dustries are summarized.